Psychiatric distress among aging decorated and non-decorated veterans: The role of impostorism and loneliness. (2nd April 2020) - Stein, Jacob Y.; Levin, Yafit; Aloni, Roy; Solomon, Zahava
Abstract: Objectives: The aging process may be affected by negative life events as well as social factors. Though psychological aspects of the aging process in veterans have been the focus of considerable research, decorated veterans have been scarcely investigated in this domain. The current study sought to assess psychiatric distress (PD) levels among aging decorated and non-decorated veterans' (DVs and n-DVs, respectively) and examine its association with the maladaptive perception that others will identify a high-achieving person as an impostor (i.e. impostorism) and perceived social isolation (i.e. loneliness). Methods: Two groups of Israeli veterans of the 1973 Yom Kippur War, DVs ( n = 75) and n-DVs ( n = 73), were assessed for PD and combat exposure in middle adulthood (1991; T1); in later life (2018; T2) they were assessed for negative life events, impostorism, loneliness and PD. Results: Impostorism, loneliness and PD were all inter-correlated. DVs evinced less PD at T1 and T2 than n-DVs but similar levels of impostorism and loneliness at T2. Nevertheless, negative life events, impostorism and loneliness explained PD at T2, with loneliness being more significant, especially among the n-DVs. Combat exposure did not explain variances in late-life PD. Conclusion: Aging DVs seem to be less vulnerable to late-life PD than n-DVs, and impostorism and loneliness may be important factors in this respect. Being the first study to investigate aging DVs' mental health and impostorism among aging veterans, the findings further underscore the clinical imperative of psychosocial factors in understanding aging veterans' mental health.